1990
DOI: 10.1128/aem.56.10.3225-3226.1990
|View full text |Cite
|
Sign up to set email alerts
|

Production of fumonisins by Fusarium moniliforme and Fusarium proliferatum isolates associated with equine leukoencephalomalacia and a pulmonary edema syndrome in swine

Abstract: Fumonisin B1 (FB1) and FB2 were isolated from corn cultures of both Fusarium moniliforme and Fusarium proliferatum. Respective concentrations in culture materials of FB1 and FB2 ranged from 960 to 2,350 and 120 to 320 ,ug/g for F. monilforme and from 1,670 to 2,790 and 150 to 320 ,Lg/g for F. proliferatum. Thin-layer chromatography, gas chromatography-mass spectroscopy, high-performance liquid chromatography, and liquid secondary ion mass spectroscopy were used for detection. Fumonisins from F. proliferatum ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
88
0
11

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(110 citation statements)
references
References 5 publications
(4 reference statements)
11
88
0
11
Order By: Relevance
“…Three Fusarium species were isolated from sprout soybean seeds in this study F. equiseti, F. chlamydosporum, and F. proliferatum. These Fusarium species are well known for producing different mycotoxins of type A and B trichothecenes, zearalenone, moniliformin, beauvericin, fusarochromanone, fusarin, and related compounds (Desjardins, 2006;Desjardins et al, 2000;Hestbjerg, Nielsen, Thrane, & Elmholt, 2002;Ivic, 2014;Ivic, Domijan, Peraica, Milicevic, & Cvjetkovic, 2009;Kosiak, Holst-Jensen, Rundberget, Gonzalez Jaen, & Torp, 2005;Langseth, 1998;Logrieco et al, 1998;Marasas, Thiel, Rabie, Nelson, & Toussoun, 1986;Park & Chu, 1993;Ross et al, 1990). Penicillium citrinum is also known for producing the mycotoxin citrinin and cellulose digesting enzymes like cellulose and endoglucanase (Khan et al, 2008).…”
Section: Fungi Species Isolated From Mfs-561 a Soybean Sprout Cultmentioning
confidence: 99%
“…Three Fusarium species were isolated from sprout soybean seeds in this study F. equiseti, F. chlamydosporum, and F. proliferatum. These Fusarium species are well known for producing different mycotoxins of type A and B trichothecenes, zearalenone, moniliformin, beauvericin, fusarochromanone, fusarin, and related compounds (Desjardins, 2006;Desjardins et al, 2000;Hestbjerg, Nielsen, Thrane, & Elmholt, 2002;Ivic, 2014;Ivic, Domijan, Peraica, Milicevic, & Cvjetkovic, 2009;Kosiak, Holst-Jensen, Rundberget, Gonzalez Jaen, & Torp, 2005;Langseth, 1998;Logrieco et al, 1998;Marasas, Thiel, Rabie, Nelson, & Toussoun, 1986;Park & Chu, 1993;Ross et al, 1990). Penicillium citrinum is also known for producing the mycotoxin citrinin and cellulose digesting enzymes like cellulose and endoglucanase (Khan et al, 2008).…”
Section: Fungi Species Isolated From Mfs-561 a Soybean Sprout Cultmentioning
confidence: 99%
“…Fumonisins are mycotoxins produced by certain strains of the molds Fusarium moniliforme Ross et al 1990) and F. proliferatum (Ross et al 1990) which are commonly found in corn and other crops . Fusarium monilijiorme toxins have been confirmed to be the cause of equine leukoencephalomalacia (ELEM) (Wilson and Maronpot 197 1;Marasas et al 1976).…”
mentioning
confidence: 99%
“…Fumonisin B1 has been shown to be the cause of ELEM (Marasas et al 1988;Ross et al 1990) and swine pulmonary edema (Harrison et al 1990;Ross et al 1990). It also has been shown to be carcinogenic in rats (Gelderblom et al 1991).…”
mentioning
confidence: 99%
“…moniliformin and fusaric acid (ABBAS et al 1991, BURMEISTER and PLATTNER 1987, CHAKRABARTI and BASUCHAUDHARY 1980, DAVIS 1969, DUKE 1986, HOAGLAND 1990, that are chemically diverse and possess a broad range of biological activities and metabolic effects. Recently, a new phytotoxin (ABBAS et al 1991) and mycotoxin (HARRISON et al 1990) called fumonisin Bi (FBi) and other related fumonisin compounds were isolated from F. moniliforme (Ross et al 1990, THIEL et al 1991, VESONDER et al 1990 and other related species of Fusarium. FBi causes phytotoxic effects such as inhibition of growth and development, necrosis, chlorosis and death to various plants including weeds (ABBAS et al 1991).…”
mentioning
confidence: 99%
“…Our results with F. moniliforme were similar to those reported for other isolates obtained from grains (corn), animal feed, etc. (GELDERBLOM et al 1992, Ross et al 1990, THIEL et al 1991. The discovery of fumonisin-producing isolates of F. moniliforme from weed plants further indicates that this fungus is indigenous to a wide variety of plants.…”
mentioning
confidence: 99%